Peran Polisi Lalu Lintas dalam Meminimalisir Penyimpangan Perilaku Melanggar Lalu Lintas di Wilayah Polsek Sukasari Kota Bandung - Hiranatasya, Hani; Danial, Endang; Masyitoh, Iim Siti (CIVICS: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2025)
Traffic violations and accidents still frequently occur in Bandung City, especially in the Sukasari Police area. The purpose of this study is to 1) determine the role of traffic police in minimizing deviant traffic violation behavior in the Sukasari Police area of ​​Bandung City, 2) determine the obstacles faced by the traffic police unit in handling the high level of traffic violations in the Sukasari Police area of ​​Bandung City, 3) determine the efforts made to overcome the obstacles faced by the traffic police unit in handling the high level of traffic violations in the Sukasari Police area of ​​Bandung City. The research method used is descriptive and literature review. The police have taken pre-emptive (deterrence), preventive (prevention) and repressive (action) actions. Although there are several obstacles in its implementation, this is still able to reduce traffic accidents in Bandung City, especially in the Sukasari Police area.